Предмет: Алгебра, автор: dima19081

Помогите пожалуйста

Приложения:

Ответы

Автор ответа: NNNLLL54
0
sqrt[5]{(frac{sqrt{8c^2}}{d})}=frac{sqrt[10]{8c^2}}{sqrt[5]{d}}=

=2^{frac{3}{10}}cdot (frac{c}{d})^{frac{1}{10}}

sqrt[5]{frac{d^9}{4c^2}}=frac{d^{frac{9}{5}}}{4^{frac{1}{5}}c^{frac{2}{5}}}=frac{d^{frac{9}{5}}}{(2c)^{frac{2}{5}}}\\frac{sqrt[6]{y^2}-4}{sqrt[6]{y}+2}=frac{(sqrt[6]{y}-2)(sqrt[6]{y}+2)}{sqrt[6]{y}+2}=sqrt[6]{y}-2\\frac{a-1}{a^{frac{1}{2}}-1}+a^{frac{1}{2}}=frac{(a^{frac{1}{2}}-1)(a^{frac{1}{2}}+1)}{a^{frac{1}{2}}-1}+a^{frac{1}{2}}=a^{frac{1}{2}}+1+a^{frac{1}{2}}=2a^{frac{1}{2}}+1
Похожие вопросы
Предмет: Математика, автор: aidynaidyn66